An assessment of the Impact of Leadership and Management on Performance of SMEs in Kurdistan - Narmen Wali Ali (International Journal on Humanities and Social Sciences, 2020)
Changes in the business environment have made it essential for businesses to abandon outdated practices and processes in favour of more progressive and efficient ones. Undoubtedly, the workforce in the current job market, technology and globalisation have impacted how businesses should be operated. The purpose of this paper is to examine the impact of management and leadership on the performance of small businesses in the Kurdistan region of Iraq. The data collected in this study show that there is a positive correlation between the application of effective management and business performance. The finding of the however point that a lot of the small business in the region, unlike the larger corporations do not have clear management strategies to guide future growth. A lot of management resources and skills currently in place are geared towards meeting short-time goals and objectives.